RANCANGAN PROTOTIPE APLIKASI BERBASIS MOBILE MENGGUNAKAN METODE DESIGN THINKING (STUDI KASUS LAYANAN AKADEMIK POLSUB) - Vernanda, Dwi; Rosid, Usep Abdul (Informatics Department-Universitas Wijaya Kusuma Surabaya, 2024)
The use of mobile-based technology today is widely used in the campus environment. Academic services are one of the services available at the Subang State Polytechnic. In it there is a process of checking the authenticity of diplomas, legalization, active lecture certificates, research permits, PKL cover letters, and college dispensation letters. The mobile-based academic service system is very important and needed to provide services that facilitate students and alumni in the campus environment because the use of mobile devices itself has become commonplace in everyday life. The purpose of this study is to design a prototype of a mobile-based application for academic services. This research uses the design thinking method which is generally used to build protoyping. This method is used to ensure the designed application meets the needs of the user and provides a better experience. Case studies are conducted in the academic services department of Subang State Polytechnic to understand existing problems and create innovative solutions. It is expected that the results of this prototype design can be applied in the future in building mobile-based applications for academic services. From the results of the entire prototype design process, it can be concluded that the prototype design of mobile-based applications can provide an overview of the academic service system at the Subang State Polytechnic.